A New Development of Multi-application of Micro-controller Through Educational Training Systems - Selvakumar, Raja Saravana Kumar; Nik Mohd Kamil, Nik Yusof; Abdalla, Ahmed N. (2009)
According to the latest survey, more than half of the total student in Faculty of Electrical & Electronics Engineering are having problem in understanding program structure and developing hardware, basically based on Intel 8051 microcontroller. The project objective is to build a development board, which could also be a learning tool for those who intend to learn microcontroller. As a development board, it could let the user to get start with their microcontroller application efficiently. Without wasting too much time in preparing prototype circuit is one of the advantages by using a development board. The Intel 8051 Microcontroller Educational Development System is also including the general application. Therefore, the users could just get start with their software construction if their applications are found in The Intel 8051 Microcontroller Educational Development System. As a learning tool, it could let the student to test their software on Intel 8051 Educational Development System. Keywords: Microcontroller, Educational, Intel 8051